Examining the Simultaneous Effects of L1 Writing, L2 Reading, L2 Proficiency, and Affective Factors on Different Task Types of L2 Writing. Issue 7 (9th August 2021) - Kim, Kyung Ja; Pae, Tae-Il
ABSTRACT: The present study examined the complex structural relationships between the factors that influence L2 writing in more and less cognitively demanding tasks. To this end, 298 10th graders were recruited from a local high school in Korea. Participants completed tasks measuring L1 and L2 writing skills, L2 reading comprehension, L2 proficiency, L2 motivation, and L2 anxiety. Data were analyzed using structural equation modeling based on a total of six sets of instruments. The results showed that for less cognitively demanding literacy tasks, L1 narrative writing skill, L2 proficiency and L2 writing anxiety had a direct impact on L2 narrative writing. L2 motivation had an indirect impact on L2 narrative writing through L2 proficiency. For more cognitively demanding tasks, L1 argumentative writing, L2 inferential reading, L2 proficiency, and L2 writing anxiety showed direct association to L2 argumentative writing. L2 motivation had an indirect effect on L2 argumentative writing through L2 proficiency and L2 inferential reading skill. These results suggest that differential sets of factors are working in tandem along the pathways to successful performance in more and less cognitively demanding literacy tasks.